2013
DOI: 10.5860/crl-236
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the Job Ad: Employers and Library Instruction

Abstract: Many content analyses of job ads have revealed the skills and experience needed in academic library jobs and show that library instruction is an important job duty. This study moves beyond the content of the job ads and surveys the employers themselves (in the person of the supervisor). The survey revealed that supervisors highly value library instruction. Other findings relate to the types of instruction duties the new employee will engage in and the ways that these employees learn how to do library instructi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 7 publications
1
23
0
Order By: Relevance
“…The library's role in the teaching of information literacy on university and college campuses has become critical to student success, with instruction increasingly becoming an important part of professional duties (Hall, 2013). Librarians often discuss information literacy in terms of students conducting research needed for academic papers, but information literacy skills are necessary for a wide-reaching range of information-seeking opportunities both in and out of the classroom.…”
Section: Information Literacy and Artmakingmentioning
confidence: 99%
“…The library's role in the teaching of information literacy on university and college campuses has become critical to student success, with instruction increasingly becoming an important part of professional duties (Hall, 2013). Librarians often discuss information literacy in terms of students conducting research needed for academic papers, but information literacy skills are necessary for a wide-reaching range of information-seeking opportunities both in and out of the classroom.…”
Section: Information Literacy and Artmakingmentioning
confidence: 99%
“…This article found the aspect of their work relating to the concepts of 'disruptive innovations' and blending of LIS, IT and pedagogical skills to respond to technology disruptions in a highly digitized higher education environment very useful. The wider literature (Walter 2008;Hall 2013;Hensley 2015) also raises the issue of the academic librarian's 'teacher identity' -both from the point of view of academic librarians themselves as well as from the perspective of students, academic staff and other university constituencies.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…This cluster, as may be observed from Table 2 and Figure 1, includes knowledge and skills that embrace the pedagogical foundations of teaching and learning. The literature is very clear that while studies have shown an increasing need for teaching skills in the digital age academic library environment, many (Miller 2007;Walter 2008;Hall 2013;Hensley 2015) have questioned whether academic librarians have the necessary grounding in the 'rudiments of pedagogy' (Hall 2013, 14) to take on these roles seriously. Are they simply being 'unceremoniously thrust into the classroom' (Walter 2008, 60) to do the best they can with what they have learnt on the job.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Auten and Twigg (2013) wrote that SoTL can benefit graduate courses by helping prepare students for the teaching in higher education. Academic librarian employers deem teaching skills an important skillset when they are looking to make a hire (Hall, 2013), and studies…”
Section: Why Include Sotl In Your Lis Classroom?mentioning
confidence: 99%